A study of serum YKL-40 and its correlation with traditional biomarkers in rheumatoid arthritis patients - Vinod Narayan; Vasanthi Pallinti; Nalini Ganesan (Indian Journal of Rheumatology)
Background: This study was aimed to measure the serum levels of YKL-40 among early and late rheumatoid arthritis (RA) patients along with other disease activity measures in RA patients. Materials and Methods: It was a cross-sectional study involving 152 RA patients based on the 1987 American College of Rheumatology criteria for the diagnosis of RA and 68 age- and sex-matched healthy controls. The patient group was further subdivided into 75 early (<2 years disease duration) and 77 late (>2 years) RA patients based on the duration of the disease. Clinical examination was performed on RA patients, and traditional markers to measure the disease activity such as Disease Activity Score (DAS)-28, Visual Analog Score (VAS), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), anti-cyclic citrullinated peptide (CCP), and rheumatoid factor (RF) were assessed. Serum YKL-40 level was measured using ELISA method. All the values were expressed as median (25th–75th percentile). Results: In our study, there was a significant increase in serum YKL-40 level in RA patients (200.8 [141.24–282.7] ng/ml) compared to healthy controls (82.2 [49.01–123.78] ng/ml) with P < 0.001. There was no significant difference in serum YKL-40 levels among early and late RA patients. The traditional inflammatory markers such as ESR, CRP, and measures of disease activity such as DAS-28 and VAS were significantly increased in late RA patients than early RA (P < 0.001). Serum YKL-40 levels were not correlated with disease activity measures such as DAS-28, VAS, CRP, and ESR in RA patients. Conclusion: Serum YKL-40 level was significantly higher in RA. However there was no difference between early and late RA. It does not correlate with measures of disease activity.